Segmentation of overlapping characters in lanna using mixed algorithm - Kosarat, Rujipan; Hiransakolwong, Nualsawat (My University, 2020)
Lanna language is a popular language in the northern part of Thailand. The segmentation of printed Lanna characters is a challenging problem. Normally, the segmentation method of characters begins with using horizontal and vertical histograms into line segmentation and character segmentation. Then, when written the output will be the correct clear characters, overlapping characters and touching characters. Frequently, there are some problems with the overlapping characters and the touching characters. This paper focuses on only the overlapping characters, overlapping between alphabets and vowels. The methods will segment the overlapping characters by histogram techniques, beginning with splitting, rotating and merging the characters. The experiments used the printed Lanna characters in many books as a data set. The results achieved an accuracy rate of 96.72%.
Keywords: Character segmentation; Merge character; Overlapping character; Rotate character; Split character